2016
DOI: 10.1016/j.molimm.2016.09.010
|View full text |Cite
|
Sign up to set email alerts
|

BET bromodomain inhibition reduces maturation and enhances tolerogenic properties of human and mouse dendritic cells

Abstract: Transcription of inflammatory genes is tightly regulated by acetylation and deacetylation of histone tails. An inhibitor of the acetylated-lysine reader bromodomain and extra-terminal domain (BET) proteins, I-BET151, is known to counteract the induction of expression of inflammatory genes in macrophages. We have investigated the effects of I-BET151 on dendritic cell function, including expression of co-stimulatory molecules and cytokines, and capacity for T cell activation. Treatment of mouse bone marrow deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 30 publications
3
41
0
Order By: Relevance
“…In recent years, BET inhibitors have attracted attention as a novel class of drug candidates not only for cancer but also for various inflammatory diseases [13, 14]. Several studies demonstrated that BET inhibitors were effective in the models of arthritis, vascular inflammation, acute pancreatitis, hepatic fibrosis and renal damage [23, 2932], as well as in T cell-transfer colitis models [21, 22]. In the present study, we demonstrated that a novel quinazoline-based bromodomain inhibitor, CN210, inhibited CBP and p300 in addition to BET proteins and that CN210 potently attenuated indomethacin-induced CD-like ileitis in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, BET inhibitors have attracted attention as a novel class of drug candidates not only for cancer but also for various inflammatory diseases [13, 14]. Several studies demonstrated that BET inhibitors were effective in the models of arthritis, vascular inflammation, acute pancreatitis, hepatic fibrosis and renal damage [23, 2932], as well as in T cell-transfer colitis models [21, 22]. In the present study, we demonstrated that a novel quinazoline-based bromodomain inhibitor, CN210, inhibited CBP and p300 in addition to BET proteins and that CN210 potently attenuated indomethacin-induced CD-like ileitis in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is known that BET proteins regulate gene transcriptions during the differentiation of naïve CD4 + cells to mature helper-T cells, and that BET inhibitors, such as JQ1, attenuated the differentiation of Th1, Th2, and Th17 cells [35, 36]. BET inhibitors have also reported to suppress inflammatory cytokine production and T-cell activation via inhibition of dendritic cell maturation and promotion of regulatory T-cell differentiation [22].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with I-BET151 reduces maturation marker and pro-inflammatory cytokine expression in dendritic cells and inhibits mature dendritic cell–mediated, antigen-dependent proliferation of naïve CD4 + T cells. 91 Dendritic cells treated with I-BET151 remain immature, and this led to increased generation of immunosuppressive Foxp3 + Tregs in vitro. Disappointingly, mice (Rag1 -/- mice transferred with CD45RB high sorted T cells) experiencing chronic colitis due to impaired Treg function displayed only modest improvement in disease symptoms when treated with I-BET151.…”
Section: Histone Readers As Therapeutic Targets For Ibdmentioning
confidence: 99%
“…Disappointingly, mice (Rag1 -/- mice transferred with CD45RB high sorted T cells) experiencing chronic colitis due to impaired Treg function displayed only modest improvement in disease symptoms when treated with I-BET151. 91 One explanation could be timing; I-BET151 administration in these mice occurred after colitis symptoms appeared and after priming of naïve T cells by dendritic cells had already occurred. Since earlier experiments negatively implicated I-BET151 in dendritic cell maturation and T cell activation, treatment with I-BET151 at an earlier stage could lead to higher Treg levels by immature dendritic cells, which might make a difference in ameliorating colitis.…”
Section: Histone Readers As Therapeutic Targets For Ibdmentioning
confidence: 99%
“…Murine cDC1s (identified as CD11b − CD103 + XCR1 + ), equivalent to CD103 + Sirpα − DCs in humans, are dependent on transcription factors (TFs) Id2, Irf8, and Batf3 and induce anti-viral/bacterial IFNγ (Th1) CD4 + T cell responses (10). In contrast, CD11b + CD103 + intestinal cDC2s are related to CD103 + Sirpα + DCs in human intestines, depend on TFs Irf4 and Notch2 (10) and are important for induction of IL-17 (Th17) and IL-4/IL-5/IL-13 (Th2) CD4 + T cell responses (11). Whether epigenetic gene regulation is important in controlling immune responses of these subsets in the gut is unknown.…”
Section: Introductionmentioning
confidence: 99%